Krisis Kualitas Tenaga Pendidik di Era Disrupsi: Transformasi Strategi Rekrutmen dan Seleksi sebagai Solusi Peningkatan Mutu - Mariyatul Kiptiyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the crisis in teacher quality in the disruption era, caused by weak recruitment and selection systems that remain administrative, subjective, and lack transparency. The research aims to analyze the need for transforming recruitment and selection strategies toward a competency- and technology-based model as a solution to improve educational quality. This research employs a qualitative approach with a case study at MTs YPI Darul Huda Belitang OKU Timur. Data were collected through interviews, observations, and documentation, then analyzed descriptively using the Miles and Huberman interactive model. Data validity was tested through source and technique triangulation. The findings reveal that implementing competency- and technology-based recruitment systems, such as e-recruitment and online assessment, enhances objectivity, transparency, and efficiency in the selection process. This transformation strengthens teacher professionalism and improves the quality of educational institutions to become more adaptive to the challenges of the digital era.